Promotion with digital media on the purchase decision of Paguh Rice - -, Veronika - (Jenderal Soedirman University, 2022)
Rice commodity becomes a challenge in online marketing. Given that rice is generally sold directly. This study aims to determine the effect of promotion and analyze the effectiveness of media promotion on digital media (facebook and instagram) of Beras Paguh with the AIDA model (Attention. Interest, Desire, and Action). The survey method was used for 100 respondents in Pontianak City by purposive sampling. Data was collected through an online questionnaire via google form. The data analysis technique used Structural Equation Modeling (SEM) through LISREL 8.80 software and the average score and simple tabulation. SEM is used to analyze the effect of digital media promotion of Paguh Rice with the AIDA model. Then the average score and simple tabulation were used to analyze the effectiveness of Paguh Rice digital media promotion. The results show that Attention and Interest have a positive effect on purchasing decisions for Paguh Rice with the most influenced indicator, namely messages, where the better the message design on digital media will be followed by higher purchasing decisions. Then in the calculation of the average score, the data shows that online promotion is quite effective on consumer purchasing decisions. This can be seen from the average value generated, which is 3.29. With this value, the promotion is declared quite effective because it is in the range of 2.61-3.40. This shows that the effective use of promotions implemented by Paguh Rice is due to the use of media that is in accordance with consumer needs and based on uploads that can attract attention until consumers finally decide to buy the product.